Cytomegalovirus reactivation in patients with refractory checkpoint inhibitor-induced colitis. (November 2017) - Franklin, Cindy; Rooms, Isabelle; Fiedler, Melanie; Reis, Henning; Milsch, Laura; Herz, Saskia; Livingstone, Elisabeth; Zimmer, Lisa; Schmid, Kurt Werner; Dittmer, Ulf; Schadendorf, Dirk; Schilling, Bastian
Abstract: Objectives: Immune checkpoint inhibitors can cause severe immune-related adverse events, with immune-related diarrhea and colitis (irColitis) being among the most frequent ones. While the majority of patients with irColitis respond well to corticosteroid treatment ± other immunomodulatory drugs such as infliximab, some patients do not show resolution of their symptoms. In the present study, we analysed the frequency of therapy-refractory irColitis, the underlying cause, and useful diagnostic approaches. Methods: Between 2006 and 2016, 370 patients with metastatic malignant melanoma were treated with checkpoint inhibitors at the Department of Dermatology at the University Hospital Essen. All patients were identified for whom diarrhea and/or colitis was documented in the digital patient records. Patients who did not respond to standard immunosuppressive therapy within 2 weeks were classified as refractory. Demographic and clinical data of all patients were collected. Results: We identified 41 patients with irColitis, the majority occurring during treatment with ipilimumab. Amongst these, 5 (12.2%) were refractory to standard immunomodulatory treatment with corticosteroids and infliximab. Therapy-refractory cases tended to show more severe inflammation in colonic biopsies (p = 0.04). In all therapy-refractory cases cytomegalovirus (CMV) was detectable. CMV-DNA in colonic biopsies and in plasma was significantly more often detectable in therapy-refractory cases (in colonic biopsies p = 0.005, in plasma: p = 0.002). Presence of serum CMV IgM and positive immunohistochemical stainings of colon biopsies for CMV were also associated with refractory colitis (p=0.021; p = 0.053). Conclusions: This report on CMV reactivation during management of checkpoint inhibitor-induced colitis emphasises the need for repetitive diagnostic measures in treatment-refractory irColitis. Highlights: Checkpoint inhibitors can cause immune-related colitis (irColitis). IrColitis can be refractory to immunosuppressive and immunomodulatory therapies. Refractory irColitis is often caused by reactivation of cytomegalovirus (CMV). CMV colitis can resolve after the application of ganciclovir. Different repetitive diagnostic measures are needed to detect CMV colitis.